Factors that Influence Audit Delay in the Trade, Service, and Investment Sector that Listed on Indonesian Stock Exchange - Rohana Dita Safitri; Ni Nyoman Alit Triani (Jurnal Akuntansi dan Keuangan, 2021)
The purpose of this study is to provide empirical evidence of the effect of company size, audit opinion, the complexity of company operations, audit tenure, and KAP specialization on audit delay. The sampling method used was purposive sampling on companies in the trade, service, and investment sectors for the period 2013-2018 and produced 447 data. The research data were analyzed using multiple linear regression analysis. The results of data analysis show that company size and audit opinion affect audit delay meanwhile, the complexity of company operations, audit tenure, KAP specialization does not affect audit delay.